Cellulite: a cosmetic or systemic issue? Contemporary views on the etiopathogenesis of cellulite - Tokarska, Kamila; Tokarski, Sławomir; Woźniacka, Anna; Sysa-Jędrzejowska, Anna; Bogaczewicz, Jarosław (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2018)
Cellulite (also known as gynoid lipodystrophy or orange peel syndrome) is one of the most common lipodystrophy syndromes, which affects millions of post-adolescent women. Cellulite is manifested by topographic disorders of subcutaneous tissue such as nodules, edema, and abnormal fibrosis. It is located mainly on the pelvic area, especially on the buttocks. Its pathogenesis is complexed and unclear. There are several theories about its pathophysiology. Hormonal disorders, endothelial dysfunction and genetic predispositions are taken under consideration.